About Synchronic and Asynchronous Organizational Forms of Distance Learning Based on Web-Technologies - Azamat Ibragimovich Tillaev (Zien Journals, 2022)
This article describes how to effectively use the software and hardware of distance learning. It also shows the newly created distance learning system for higher education based on web technologies and its components and capabilities
Keywords: distance learning; seminar; synchronous seminar; chat seminar